(untitled) - Hallaq, Wael B. (Cambridge, UK,New York, 2001)
In his latest book, Wael Hallaq examines the relationship between authority, continuity and change. He demonstrates how the authority of the law schools and their founders maintained school methodology and hermeneutics. It was this environment that gave rise to a variety of individual legal opinions, ultimately legitimizing changes in the law. Thus the author concludes that the mechanisms of change are embedded in the very structure of Islamic law, despite its inherent conservatism. Scholars and specialists will welcome the intellectual rigor and innovation of this pathbreaking analysis
Keywords: Islamic law,Luật hồi giáo; Interpretation and construction